(untitled) (De Legibus - Law Journal, 2022)
The constitutional guarantee of job security and the prohibition of dismissals without just cause, provided by the 53th article of the Portuguese Constitution, does not legitimize the usurpation and offense of the courts power by administrative entities, which, if it occurs, may result in the nullity of their activity. Those, as organs of sovereignty with the responsibility to administrate justice on behalf of the people, under the terms of paragraphs 1, 2 and 3 of 202nd article, of the Portuguese Constitution, are responsible for ensuring the defense of legal and protected rights and interests of the citizens, even if assisted by other authorities, as long as the guarantee of separation of powers, stipulated in the 2nd of the Portuguese Constitution, is not disrespected.